STUDY OF THE EFFECT OF TEACHER EFFICACY ON THE EDUCATIONAL ACHIEVEMENT AND EMOTIONAL DEVELOPMENT OF MIDDLE LEVEL STUDENTS - Verma, Madhu; Pandey, Mahendra Prasad (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Students and education have a very deep relationship with each other. Education is more important than food for achievement. The present research paper is based on the study of the effect of teacher efficacy of teachers on the emotional development of middle level students. Where children are the center of school education, a teacher plays the most important role in ensuring knowledge acquisition in children. Education widely affects the socio-economic status of any society. Teacher-teaching process effectiveness, emotional development of teacher's emotional intelligence etc. affect.